The Impact of Financial Proficiency, Financial Attitudes, and Income on Financial Behavior in Using PayLater on E-Commerce - Nur Komarudin, Munir; Arraniri, Iqbal; Agyan, Dea Fadhila (International Journal Administration, Business & Organization, 2024)
This research aims to determine the influence of financial proficiency, financial attitudes and income on the financial behavior of using Paylater in millennial generation E-Commerce in Kuningan. The research method used is descriptive with a quantitative approach. The sampling technique used was non-probability sampling with an incidental sampling and purposive sampling approach totaling 400 respondents. Data collection was carried out by distributing questionnaires in the form of a Google form. Hypothesis testing in this research uses multiple linear analysis tests. The research results show that financial literacy, financial attitudes and income have a positive effect on financial behavior.